العلاقة بين الأسلوبية والبلاغة بين القديم والحديث: دراسة وصفية تطبيقية (The relations between stylistics and eloquence in the past and modern era: A Descriptive and Practical Study) - (Evren Zari'), آفرين زارع (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث الأسلوبية فرع من اللسانيات ووليدة علم اللغة، تغذت من البلاغة القديمة وعلی خلاف زعم بعض الباحثين الغربيين الذين يعدون الأسلوبية وليدة الغرب وأوروبا، يری الباحثون العرب جذورها في البلاغة القديمة وعلم اللغة، والنقد الأدبي، ولکن کانت هذه المعلومات منزوية عبر السنوات السابقة حتی تطورت بتطورعلم اللغة الحديث، وانضمت هذه العلوم تحت لوائها وتوسعت مداها، ولم تکتف بهذه العلوم، بل تطرقت إلی علوم أخری نحو علم الاجتماع وعلم النفس وغيرهما. هذه المقالة تختار علم البلاغة من بين العلوم المرتبطة بالأسلوبية، وتبحث عن وجوه التشابه والخلاف بينهما حتی تکشف عن العلاقات الوطيدة بينهما عبر الدراسات التطبيقية، والتحليل الأدبي في سورة طه، وتتناول مدی فاعلية التحليل البلاغي والتحليل الأسلوبي في کشف أسرار القرآن الکريم. إن من أهم النتائج التي توصلت إليها المقالة هذه هي: أن للبلاغة دورها في التحليل الأدبي لکنها قصيرة اليد ضيقة المجال مقارنة بالأسلوبية التي يکون نطاقها أوسع، وتعتبر البلاغة فرعا لها. الكلمات المفتاحية:الأسلوبية-البلاغة-التشابه-الاختلاف-الدراسات التطبيقية Abstract Stylistics is a branch from linguistics and an outcome of linguistics. It comes from the classic rhetoric despite the claim of some of the western researches that it was a o Western and European product. On the contrary, Arab researchers viewed it as an offshoot of the classic rhetoric, linguistics and traditional criticism. But this view was held back since years ago until it developed with the progress of contemporary linguistics flourishing itself under those banners. It further consolidated with other disciplines such as psycholinguistic and sociolinguistic, to name a few. This article chooses rhetoric from among the disciplines related to stylistics among other knowledge that has a link with stylistics, and it discovers the similarities. It endeavors to uncover the differences between them to establish the close relation between the two through applied studies, literary study of surah taha. It discusses about the impact of rhetorical analysis and stylistic analysis in uncovering the secrets of the Al-Qur’an Al-kareem. Among the most important results that has been discovered in this article are: Rhetoric has a role in literature analysis but it is narrow and restricted compared to stylistics which has a wider range with the inclusion of rhetoric as one of its branch. Keywords: Stylistics - Rhetoric - Similarities - Differences – Applied Studies. Abstrak Gayabahasa adalah satu cabang linguistik yang dijana retorik lama, tidak seperti yang dikatakan oleh sesetengah pengkaji barat yang menganggap bahawa gayabahasa (stailistik) lahir dari barat dan Eropah. Para pengkaji Arab berpendapat bahawa akar umbinya berasal daripada retorik lama, liuguistik dan kritikan sastera. Namun, maklumat ini terpendam bertahun-tahun yang lalu sehinggalah ia berkembang sejajar dengan perkembangan linguistik moden yang mana kesemua cabang ilmu ini bergabung lalu berkembang di bawahnya, bukan setakat itu sahaja, malah ia juga telah mencakupi bidang lain seperti sosiologi psikologi dan sebagainya. Artikel ini memilih bidang retorik daripada lain-lain bidang berkaitan stailistik, akan mencari persamaan dan perbezaan seterusnya hubungan kuat antara keduanya melalui kajian –kajian aplikasi dan analisa kesusasteraan dalam surah Ţāhā.Ia juga akan melihat tahap keberkesanan analisa retorik dan stailistik dalam mencari rahsia-rahsia al-Qur’ān. Antara dapatan penting kajian ialah: sungguhnpun retorik memainkan peranan dalam analisa kesusasteraan, skopnya adalah lebih kecil berbanding stailistik yang lebih luas. Dengan itu retorik dianggap sebagai salah satu cabang stailistik. Kata kunci: Stailistik – retorik - persamaan – perbezaan – kajian aplikasi